Comprehensive Analysis of the Tumor Microenvironment and Ferroptosis-Related Genes Predict Prognosis with Ovarian Cancer - Li, Xiao-xue; Xiong, Li; Wen, Yu; Zhang, Zi-jian (Frontiers in Genetics, 2021)
The early diagnosis of ovarian cancer (OC) is critical to improve the prognosis and prevent recurrence of patients. Nevertheless, there is still a lack of factors which can accurately predict it. In this study we focus on interaction of immune infiltration and ferroptosis, and selected ESTIMATE algorithm and 15 ferroptosis-related genes (FRGs) to construct a novel E-FRGs scoring model for predicting overall survival of OC patients. Gene expression and corresponding clinical characteristics were obtained from TCGA dataset (n =375), GSE18520 (n =53) and GSE32062 (n = 260). A total of 15 FRGs derived from FerDb with Immunescore and Stromalscore were identified in the prognostic model by using least absolute shrinkage and selection operator (LASSO) penalized COX regression analysis. The Kaplan-Meier survival analysis and time-dependent ROC curves performed a powerful prognostic ability of the E-FRGs model via multi validation. Gene set enrichment analysis and Gene set variation analysis elucidate multiple potential pathways between the high and low E-FRGs score group. Finally, the proteins of different genes in the model were verified in drug-resistant and non-drug-resistant tumor tissues.Results of this research provide new prospects in the role of immune infiltration and ferroptosis as a helpful tool to predict the outcome of OC patients.